2015
DOI: 10.1002/hyp.10529
|View full text |Cite
|
Sign up to set email alerts
|

Contributing sources to baseflow in pre‐alpine headwaters using spatial snapshot sampling

Abstract: Mountainous headwaters consist of different landscape units including forests, meadows and wetlands. In these headwaters it is unclear which landscape units contribute what percentage to baseflow. In this study, we analysed spatiotemporal differences in baseflow isotope and hydrochemistry to identify catchment-scale runoff contribution. Three baseflow snapshot sampling campaigns were performed in the Swiss pre-alpine headwater catchment of the Zwäckentobel (4.25km2) and six of its adjacent subcatchments. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
73
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 40 publications
(85 reference statements)
13
73
0
Order By: Relevance
“…The PCA is an explorative analysis which enables to reduce number of predictors and to classify them among principal components which capture the much of the variance of the original dataset (Fischer et al, 2015;López-Moreno and Latron, 2008;Revuelto et al, 2016). A set of mutually correlated variables are transformed into a set of uncorrelated variables (principal components, PC) which are ordered by reducing variability.…”
Section: Bivariate and Multivariate Statistical Analysesmentioning
confidence: 99%
“…The PCA is an explorative analysis which enables to reduce number of predictors and to classify them among principal components which capture the much of the variance of the original dataset (Fischer et al, 2015;López-Moreno and Latron, 2008;Revuelto et al, 2016). A set of mutually correlated variables are transformed into a set of uncorrelated variables (principal components, PC) which are ordered by reducing variability.…”
Section: Bivariate and Multivariate Statistical Analysesmentioning
confidence: 99%
“…However, the within catchment variability in stream chemistry during the three baseflow snapshot sampling campaigns was large (Fischer et al, 2015). DOC concentrations were much higher in the wetlands than in areas with other land uses.…”
Section: Streamflow Chemistry During Baseflow Conditionsmentioning
confidence: 88%
“…Together with the stable isotope data (representing the water itself), the DOC and calcium data helped to identify the different end-members: an upper spring zone (above 1400 m a.s.l. ), shallow groundwater, and wetlands (Fischer et al, 2015). Stream samples had a distinctly different isotopic and hydrochemical composition than the groundwater in the wetlands and suggested that despite these areas being water-logged, they did not contribute significantly to baseflow (Fischer et al, 2015).…”
Section: Streamflow Chemistry During Baseflow Conditionsmentioning
confidence: 98%
See 2 more Smart Citations